High-concentration carbamide peroxide can reduce the sensitivity caused by in-office tooth bleaching: a single-blinded randomized controlled trial - Aline Carvalho PEIXOTO; Savil Costa VAEZ; Natalia Andrade de Resende PEREIRA; Carla Nogueira da Silva SANTANA; Karla Danielly Alves SOARES; Ana Clara Teles Roriz ROMÃO; Lorena Fernandes FERREIRA; Paulo Ricardo Saquete MARTINS-FILHO; André Luis FARIA- (University of São Paulo, 2018)
Abstract Objectives A single-blinded, randomized, parallel clinical trial evaluated the use of 37% carbamide peroxide (CP) on bleaching effectiveness and tooth sensitivity reported by patients undergoing in-office tooth bleaching, in comparison with the results of using 35% hydrogen peroxide. Material and Methods Forty patients were allocated to receive two sessions of in-office tooth bleaching using either 35% hydrogen peroxide (HP) or 37% CP. Each patient's sensitivity level was evaluated during and up to 24 h after bleaching. The effectiveness of the bleaching procedures was evaluated with a spectrophotometer one week after each session and 30 days after the last session. The impact of tooth bleaching on the patients' perceptions regarding smile changes, in addition to the bleaching procedures and their results, were also recorded. Absolute and relative sensitivity risks were calculated. Data on sensitivity level were analyzed using the Mann-Whitney or T-test, and data from the color evaluation were subjected to 2-way repeated measures ANOVA. Results The use of CP reduced the risk and level of tooth sensitivity to values close to zero, whereas the difference between the bleaching agents disappeared after 24 h. An increased bleaching effect was observed for HP, mainly due to an improved reduction of redness and yellowness. Participants perceived improved tooth bleaching for HP and reduced sensitivity for CP, but no differences regarding the comfort of the techniques were noted. Conclusions In our study, 37% CP resulted in reduced tooth sensitivity but decreased the tooth bleaching effectiveness. However, both bleaching agents resulted in high levels of patient satisfaction.